Managerial Compensation and the Market Reaction to Bank Loans - Almazan, Andres; Suarez, Javier (Review of Financial Studies, 2003)
Wklv sdshu frqvlghuv zk| d pdqdjhu zrxog fkrrvh wr vxeplw klpvhoi wr wkh glvflsolqh ri